2015
DOI: 10.1177/0165551515569651
|View full text |Cite
|
Sign up to set email alerts
|

A user-profile-based friendship recommendation solution in social networks

Abstract: Today, OSNs (online social networks) have become a popular communication platform, and a wide range of applications are considered for them. One fundamental relationship among members of a social network is friendship. Friend matching is a reasonable way to suggest people to each other. In this paper, we propose a model for measuring the similarities of two members based on information contained in their profiles. Unlike other profile-matching models, we do not assign equal weights to different items in users’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Currently, recommender systems exist in new domains. Examples include Mazhari et al (), who proposed a friendship recommender system for social networks on the basis of user profiles. The recommender system uses a similarity measure to determine the degree of similarity between two users on the basis of their profiles.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, recommender systems exist in new domains. Examples include Mazhari et al (), who proposed a friendship recommender system for social networks on the basis of user profiles. The recommender system uses a similarity measure to determine the degree of similarity between two users on the basis of their profiles.…”
Section: Related Workmentioning
confidence: 99%
“…Recommender systems are used to suggest items to users based on their interests. They have been used in various domains such as market recommenders (Wei, Moreau, & Jennings, ), book recommenders (Mooney, Bennett, & Roy, ), article recommenders (Resnick, Iacovou, Suchak, Bergstrom, & Riedl, ), and social network friendship recommenders (Mazhari, Fakhrahmad, & Sadeghbeygi, ). In this paper, we focus on movie recommenders, where the items are movies and the users are online store clients.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks have become an integral, part of our daily lives, enabling us to keep in touch with our friends and families [1]. The existing models incorporate either node profile attributes or link formation information or both [2]. Most of them represent the members and relationships among them in the form of a mathematical graph with nodes as vertices and ties as edges.…”
Section: Related Workmentioning
confidence: 99%
“…A hybrid similarity measure that combines network similarity with node profile similarityhas been proposed in reference [5].A brief survey in reference [6] illustrates the variety of similarity measures developed for social networks and the difficulty of selecting a similarity measure for problems such as link prediction or community detection. The friendship recommendation system proposed in reference [2] employed different similarity metrics for various features. When applied to real world social network data, it suggested that interest, age, gender, and location contribute to friendship formation.…”
Section: Profile Matchingmentioning
confidence: 99%
See 1 more Smart Citation